Stunting dan perkembangan anak usia 12-60 bulan di Kalasan - Hardiana Probosiwi; Emy Huriyati; Djauhar Ismail (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
PurposeThis study determine the relationship between stunting incidence with development in children aged 12-60 months.MethodsThe type of research used was observational with cross sectional study design. This research will be conducted in the working area of Puskesmas Kalasan Sleman regency Yogyakarta with subject children aged 12 to 60 months as many as 106 children. Data analysis with univariable, bivariable with chi-square test with significance level of p <0,05 and CI 95% and multivariable by using statistical test of logistic regression.ResultsBivariable analysis between stunting status and child development showed significant relationship (p <0,05) and OR 3,9 (95% CI; 1,8-8,9). The result of the multivariable analysis is the relationship between stunting status and the development of children aged 12-60 months who consider the energy intake.ConclusionsThere is a relationship between stunting and the development of children aged 12-60 months but between maternal education, infectious diseases, parenting, energy intake, long-term birth, and parental income, energy intake most closely related to child development when jointly considered.